Clinical significance of matrix metalloproteinase (MMP)-2 and MMP-9 expression in laryngeal squamous cell carcinoma - Rašić Dejan; Perić Aleksandar; Vukomanović-Đurđević Biserka; Sotirović Jelena; Baletić Nenad; Milojević Milanko; Pavićević Ljubomir; Dimić Aleksandar (Vojnosanitetski Pregled)
Background/Aim. The previous researches suggest that matrix metalloproteinases (MMPs) have the ability to degrade extracellu-lar matrix components and play an important role in malignant tumour progression and metastasis. The aim of this study was to investigate MMP-2 and MMP-9 expression in the tissue of laryn-geal squamous cell carcinoma (LSCC) and to evaluate their clini-cal significance. Methods. In this prospective study the samples of tumour tissue of seventy patients with LSCC (45 glottic and 25 supraglottic), and samples of laryngeal mucosa of 70 patients with chronic laryngitis were immunohistochemically stained for MMP-2 and MMP-9. We studied the relationships between MMPs tissue expression and clinical and histological characteris-tics of the patients with LSCC in comparison to the patients with chronic laryngitis. Results. MMP-2 and MMP-9 expression was significantly higher in the tissue of both glottic and supraglottic LSCC than in chronically inflamed laryngeal mucosa (p < 0.001 and p < 0.001, respectively). There were positive correlations be-tween epithelial MMP-2 expression and the presence of perineu-ral invasion (r = 0.515, p < 0.008), lymphovascular invasion (r = 0.559, p < 0.004) and disease recurrence (r = 0.415, p < 0.039) in supraglottic LSCC, as well as between MMP-2 expression and the presence of the exophytic type of tumour growth (r = 0.347, p < 0.020) in glottic LSCC. Epithelial MMP-9 expression was as-sociated with lymphovascular invasion (r = 0.331, p < 0.026) and the presence of the exophytic tumour growth (r = 0.474, p < 0.001) in glottic LSCC. Conclusion. MMP-2 and MMP-9 can be used as potential biomarkers for the assessment of LSCC progression.